Evaluating the current breadth of randomized control trials on cardiac arrest: A scoping review - Jake Toy; Lauren Friend; Kelsey Wilhelm; Michael Kim; Claire Gahm; Ashish R. Panchal; David Dillon; Joelle Donofrio‐Odmann; Juan Carlos Montroy; Marianne Gausche‐Hill; Nichole Bosson; Ryan Coute; et al. (Journal of the American College of Emergency Physicians Open)
Abstract Objectives Despite the significant disease burden due to cardiac arrest, there is a relative paucity of randomized controlled trials (RCTs) to inform definitive management. We aimed to evaluate the current scope of cardiac arrest RCTs published between 2015 and 2022. Methods We conducted a search in October 2023 of MEDLINE, Embase, and Web of Science for cardiac arrest RCTs. We included trials published between 2015 and 2022 enrolling human subjects suffering from non‐traumatic cardiac arrest. Descriptive statistics were reported and the Mann Kendall test was used to evaluate for temporal trends in the number of trials published annually. Results We identified 1764 unique publications, 87 RCTs were included after title/abstract and full‐text review. We found no significant increase in trials published annually (eight in 2015 and 16 in 2022, p = 1.0). Geographic analysis of study centers found 31 countries represented; Denmark (n = 13, 15%) and the United States (n = 9, 10%) conducted the majority of trials. Nearly all trials included adults (n = 84, 97%) and few included children (n = 9, 10%). The majority of trials focused on out‐of‐hospital cardiac arrest (n = 62, 71%). Thirty‐eight (44%) trials used an intervention characterized as a process improvement; 28 (32%) interventions were characterized as a drug and 20 (23%) as a device. Interventions were implemented with similar frequency in the prehospital (33%) and intensive care unit (38%) setting, as well as similarly between the intra‐arrest (53%) and post‐arrest (46%) periods. Twenty (27%) trials selected a primary outcome of survival at ≥ 28 days. Conclusions Publication of cardiac arrest RCTs remained constant between 2015 and 2022. We identified significant gaps including a lack of trials examining in‐hospital cardiac arrest and pediatric patients.